China's Rule of Law Index 2017 (Singapore : Springer Singapore, 2018)
This book investigates and evaluates the indexes of Government Transparency, Judicial Transparency, Procuratorial Transparency, and Legislation by Local People's Congresses in China. It explores a representative case study on the Rule of Law in Yuhang District of Hangzhou City, assesses the progress made and remaining problems in the implementation of these systems, and puts forward suggestions on how they could be improved in the future.
Introduction: Evaluating the Level of Rule of Law: Methods and Approaches -- Rule of Law in China 2016-2017: Review and Outlook -- Chinese Government Transparency Index Report (2015) -- Chinese Government Transparency Index Report (2016) -- China Judicial Transparency Index Report (2015) -- China Judicial Transparency Index Report (2016) -- China Maritime Judicial Transparency Index Report (2015) -- China Maritime Judicial Transparency Index Report (2016) -- Beijing Court Judicial Transparency Index Report (2015) -- Zhejiang Court Judicial Transparency Index Report (2015) -- China Procuratorial Transparency Index Report (2015) -- China Procuratorial Transparency Index Report (2016).
Law and Criminology
text file PDF
Keywords: Private international law; Conflict of laws; Law-Philosophy.; Law; Constitutional law